Analytic calculation of touch and leakage currents of non-isolated EV chargers using a fast common mode calculation method and non-ideal passive component models - Stutz, Christian; Nielebock, Sebastian; März, Martin (24th European Conference on Power Electronics and Applications, EPE 2022 ECCE Europe, 2022)
Non-isolated charging systems suffer from tremendous touch currents due to the significant extension of the common mode coupling path by the electric vehicle. Since safety limits are very tough, the selection of converter topology, modulation scheme and filters with respect to touch current behavior is a very ambitious process. With the aim to ease integral system design, research is done for common mode analysis methods, eliminating the demand for long duration time domain simulations. A time saving method to analyze the touch current behavior in common mode domain is applied on a single stage charging system setup by a 3-level converter, filter system and a major coupling path. Furthermore, this paper improves that time-saving failure current prediction method by including the influence of non-ideal passive component models on the calculation result. All calculation results are compared to laboratory measurements. Border conditions from corresponding standards are used to define the required frequency range. Besides the touch current, which typically occurs during the failure condition of a broken protective earth conductor, the leakage current flowing in the protective earth conductor during normal operation is analyzed. Finally, this paper points out the influence of an internal common mode bypass via the filter system on the touch and leakage current.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Automotive component; Battery charger; Charging infrastructure for EV's; Failure modes; Grid-connected inverter; Non-isolated EV chargers; Power converters for EV; Simulation

Applying a Fast Analytic Calculation Method in CM Domain for Touch Currents to a Two-Stage Charging Infrastructure - Stutz, Christian; März, Martin; Nielebock, Sebastian (EPE'23 ECCE Europe, 2023)

Intrinsische Common Mode Kompensation eines 2-stufigen E-Car-Ladesystems ohne galvanische Trennung - März, Martin; Stutz, Christian; Nielebock, Sebastian (Elektrik & Elektronik in Hybrid- und Elektrofahrzeugen - EEHE, 2023)
Galvanisch nicht getrennte Ladesysteme bieten Vorteile bezüglich des Gewichts, der Kosten und Effizienz, da sie keinen Transformator benötigen. Andererseits weisen diese Systeme erhöhte Berührströme auf Grund der starken Erweiterung des Common Mode (CM) Koppelpfades durch die Y-Kapazitäten des E-Fahrzeugs (EV) auf. Deren treibende Quelle ist die CM-Spannung (CMV) des Active Front Ends (AFE). Somit wird der störstrom durch die Wahl der Pulsweitenmodulation (PWM) unmittelbar beeinflusst. Eine PWM einzusetzen, welche hinsichtlich ihres CM-Verhaltens optimiert ist, ist eine praktische Ansatz, um die Ströströme zu reduzieren, aber andere Eigenschaften wie beispielsweise der Rippel des Netzstromes oder der lineare Bereich der Ausgangsspannung können dadurch nachteilig beeinflusst werden. Ladegeräte verfügen typsicherweise über einen DC-DC-Wandler (DC-DC) in der zweiten Stufe, um die vom E-Fahrzeug angefragte Ladespannung und den Ladestrom bereit zu stellen. Diese Einheit bietet einen Freiheitsgrad bezüglich ihrer CMV. Dieser erlaubt es, die CMV des AFE zu kompensieren und erleichtert dadurch die Auswahl der PWM für das AFE. Innerhalb dieser Arbeit wird die Realisierung dieses Ansatzes für ein 3-phasiges 2-Level-AFE und einen H-Brücken-DC-DC beschrieben. Die benötigten Formeln und Timing Diagramme werden hergeleitet, simulative Ergebnisse und praktische Labormessungen für verschiedene Space Vector PWM (SVPWM) präsentiert.